Sponsorship, executive coaching and the career progression of black women in the banking sector in Gauteng - Legote, Tebogo (University of the Witwatersrand, Johannesburg, 2023)
The banking sector transformation journey is not vastly different from other industries that are male dominated. With the increasing number of women joining the workforce, there is great demand for institutions to diversify and improve upon the representation of women in senior, decision making roles. Not only is this a legislative requirement, transformation is enshrined in the charter. Black women continue to be a marginalised group, as evident in a number of studies that highlight the challenges experienced by black women. The study sought to understand how sponsorship and executive coaching alleviates such challenges, and the effect of the sponsorship in the coaching process. Using an interpretive inductive approach to the study, a qualitative research methodology was applied to collect data from ten senior and executive managers, using semi-structured interviews as a tool. The phenomenological study enabled the collection of informative insights, shedding light on experiences of black women, of sponsorship and executive coaching. Information obtained from the interviews was analysed employing thematic analysis and fourteen themes and several sub-themes surfaced. The findings illustrated positively career advancement as a result of sponsorship, however, no evidence showed sponsorship influence on the coaching process. The study concludes that sponsorship and executive coaching can enable career progression for black women in the banking sector. The study recommends that in order to understand the plight of women in the workplace, unconscious biases should be dispelled. The recommendation also draws attention to the significant role that sponsors can play in advocating for gender equity in general not limited to managing the careers of a few
A research report submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Business and Executive Coaching Wits Business School Johannesburg, 202
Keywords: Sponsorship; Career progression; Executive coaching; UCTD; SDG-5: Gender equality